A rapid and convenient derivatization method for quantitation of short‐chain fatty acids in human feces by ultra‐performance liquid chromatography/tandem mass spectrometry. (1st March 2020) - Fu, Huan; Zhang, Qing‐li; Huang, Xiao‐wu; Ma, Zheng‐hua; Zheng, Xiao‐li; Li, Shi‐lin; Duan, Hao‐nan; Sun, Xiao‐chu; Lin, Fei‐fei; Zhao, Li‐juan; Teng, Guo‐sheng; Liu, Jia
Abstract : Rationale: Short‐chain fatty acids (SCFAs) are associated with intestinal microbiota and diseases in humans. SCFAs have a low response in mass spectrometry, and in order to increase sensitivity, reduce sample consumption, shorten analysis time, and simplify sample preparation steps, a derivatization method was developed. Methods: We converted seven SCFAs into amide derivatives with 4‐aminomethylquinoline. The reaction occurred for 20 min at room temperature. The analytes were separated on a reversed‐phase C18 column and quantitated in the positive ion electrospray ionization mode using multiple reaction monitoring. Acetic acid‐d4 was used as the stable‐isotope‐labeled surrogate analyte for acetic acid in the working solutions, while the other stable‐isotope‐labeled standards were used as internal standards (ISs). Results: Method validation showed that the intra‐day and inter‐day precision of quantitation for the seven SCFAs over the whole concentration range was ≤3.8% ( n = 6). The quantitation accuracy ranged from 85.5% to 104.3% ( n = 6). Most important, the collected feces were vortexed immediately with ethanol. Conclusions: This study provides a new derivatization method for a precise, accurate, and rapid quantitation of SCFAs in human feces using ultra‐performance liquid chromatography/tandem mass spectrometry. This method successfully determined the concentration of SCFAs in human feces and could assist in the exploration of intestinal microbiota and diseases.